A 3‐miRNA signature predicts survival of patients with hypopharyngeal squamous cell carcinoma after post‐operative radiotherapy. Issue 12 (2nd October 2019) - Xu, Xinbo; Lu, Zhongming; Gross, Neil; Li, Guojun; Zhang, Fenghua; Lei, Dapeng; Pan, Xinliang
Abstract: Since the prognosis of hypopharyngeal squamous cell carcinoma (HSCC) remains poor, identification of miRNA as a potential prognostic biomarker for HSCC may help improve personalized therapy. In the 2 cohorts with a total of 511 patients with HSCC (discovery: N = 372 and validation: N = 139) after post‐operative radiotherapy, we used miRNA microarray and qRT‐PCR to screen out the significant miRNAs which might predict survival. Associations of miRNAs and the signature score of these miRNAs with survival were performed by Kaplan‐Meier survival analysis and multivariate Cox hazard model. Among 9 candidate, miRNAs, miR‐200a‐3p, miR‐30b‐5p, miR‐3161, miR‐3605‐5p, miR‐378b and miR‐4451 were up‐regulated, while miR‐200c‐3p, miR‐429 and miR‐4701 were down‐regulated after validation. Moreover, the patients with high expression of miR‐200a‐3p, miR‐30b‐5p and miR‐4451 had significantly worse overall survival (OS) and disease‐specific survival (DSS) than did those with low expression (log‐rank P < .05). Patients with a high‐risk score had significant worse OS and DSS than those with low‐risk score. Finally, after adjusting for other important prognostic confounders, patients with high expression of miR‐200a‐3p, miR‐30b‐5p and miR‐4451 had significantly high risk of overall death and death owing to HSCC and patients with a high‐risk score has approximately 2‐fold increased risk in overall death and death owing to HSCC compared with those with a low‐risk score. These findings indicated that the 3‐miRNA‐based signature may be a novel independent prognostic biomarker for patients given surgery and post‐operative radiotherapy, supporting that these miRNAs may jointly predict survival of HSCC.